Observations of the Biology and Ecology of the Black-Winged Termite, Odontotermes formosanus Shiraki (Termitidae: Isoptera), in Camphor, Cinnamomum camphora (L.) (Lauraceae). (10th April 2012) - Appel, Arthur G.; Hu, Xing Ping; Zhou, Jinxiang; Qin, Zhongqi; Zhu, Hongyan; Chang, Xiangqian; Wang, Zhijing; Liu, Xianqin; Liu, Mingyan
Abstract : Aspects of the biology and ecology of the black-winged termite, Odontotermes formosanus Shiraki, were examined in a grove of camphor trees, Cinnamomum camphora (L.), located at the Fruit and Tea Institute, Wuhan, China. Of the 90 trees examined, 91.1% had evidence of termite activity in the form of exposed mud tubes on the bark. There was no relationship between tree diameter and mud tube length. Mud tubes faced all cardinal directions; most (60%) trees had multiple tubes at all directions. However, if a tree only had one tube, 22.2% of those tubes faced the south. The majority (>99%) of mud tubes were found on the trunk of the tree. Approximately 35% of all mud tubes had termite activity. Spatial distribution of termite activity was estimated using camphor and fir stakes installed throughout the grove. Camphor stakes were preferred. Kriging revealed a clumped distribution of termite activity.